POET Psalm 144 Integrating Exegesis with Poetic Devices for Effectiveness and Compositional Unity - Boerger, Brenda H. (2025)
The POET Psalms English translation of Ps 144 follows a poetic form that can be sung. I use this translation to highlight the application of twelve principles I propose for translating biblical poetry. I also advocate for adopting alternative exegetical decisions in difficult verses when it increases coherence, as opposed to tacitly accepting the status quo. Then, using this alternative, but equally valid, exegesis, I show how the curtal sonnet poetic form, related poetic devices, and a suggested tune all contribute to Ps 144’s overall effectiveness as a unified English composition. I conclude that heightened language translations should be considered best practice in the translation of biblical poetry and suggest approaches to doing so in languages other than English.
Keywords: literary devices; local genres; reexamining conventional exegesis; poetic translation